2021
DOI: 10.33263/briac125.67536762
|View full text |Cite
|
Sign up to set email alerts
|

Imunosuppresive Activity of Momordica charantia L. fruit extract on the NF-κB pathway in Drosophila melanogaster

Abstract: The activation of the NF-kB pathway leading to the production of proinflammatory cytokines is a critical feature in innate antiviral immunity. However, in SARS-CoV-2 infection, a high number of cases with a prolonged late-stage stimulation of cytokine production that leads to a cytokine storm phenotype, an undesirable, dangerous immune-related state that can cause multiple organ failures, have been reported. To treat this, immunosuppressants with selective action on the innate NF-kB pathway are urgently requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Autoinflammatory phenotypes can be observed in an experimental model organism, including the PGRP-LB Δ D. melanogaster. Previously, the authors' group showed that the PGRP-LB Δ flies have shorter lifespans than their Oregon R wildtype counterparts (Asfa et al, 2022;Nainu et al, 2022). This is probably due to the loss of the PGRP-LB protein which functions as a negative regulator of the Imd pathway in D. melanogaster (Orlans et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autoinflammatory phenotypes can be observed in an experimental model organism, including the PGRP-LB Δ D. melanogaster. Previously, the authors' group showed that the PGRP-LB Δ flies have shorter lifespans than their Oregon R wildtype counterparts (Asfa et al, 2022;Nainu et al, 2022). This is probably due to the loss of the PGRP-LB protein which functions as a negative regulator of the Imd pathway in D. melanogaster (Orlans et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the loss of the PGRP-LB protein that plays an important function in the homeostatic regulation of the NF-kB pathway, Relish, in D. melanogaster. In the absence of this PGRP-LB protein, overexpression of immune-related genes, under the Imd (NF-κB) pathway was observed (Kounatidis et al, 2017;Asfa et al, 2022;Nainu et al, 2022). Based on the observation of the survival assay, the PGRP-LB Δ flies in the untreated control group succumbed up to 100% on day 30, while on the same day, there were still live PGRP-LB Δ in the curcumin-treated groups at all concentrations.…”
Section: Curcumin Improved the Lifespan Of Pgrp-lb δ D Melanogastermentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of PGRP-LB has been demonstrated to stimulate overactivation of the NF-κB (IMD) pathway in flies. They found that the extract enhanced the survival and locomotion of PGRP-LB mutants in a concentration-dependent manner and reduced the expression of Dpt and Dro , the downstream genes in the IMD pathway [ 59 ].…”
Section: Examples Of Studies To Test the Immunomodulatory Effect Of P...mentioning
confidence: 99%